2008
DOI: 10.1093/brain/awn065
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of progressive supranuclear palsy and multiple system atrophy

Abstract: Prognostic predictors have not been defined for progressive supranuclear palsy (PSP) and multiple system atrophy (MSA). Subtypes of both disorders have been proposed on the basis of early clinical features. We performed a retrospective chart review to investigate the natural history of pathologically confirmed cases of PSP and MSA. Survival data and several clinically relevant milestones, namely: frequent falling, cognitive disability, unintelligible speech, severe dysphagia, dependence on wheelchair for mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
281
6
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(329 citation statements)
references
References 40 publications
30
281
6
5
Order By: Relevance
“…In our study, this association was confirmed by differences found in the survival analysis based on onset symptoms. Other studies have reported that patients with autonomic failure at disease onset had worse prognoses than those that exhibited cerebellar ataxia at onset [19,20]. In the current study, we found the same association even though the definition of autonomic failure in the national registry might be different from that in previous studies.…”
Section: Sakushima Et Al Page 10supporting
confidence: 59%
“…In our study, this association was confirmed by differences found in the survival analysis based on onset symptoms. Other studies have reported that patients with autonomic failure at disease onset had worse prognoses than those that exhibited cerebellar ataxia at onset [19,20]. In the current study, we found the same association even though the definition of autonomic failure in the national registry might be different from that in previous studies.…”
Section: Sakushima Et Al Page 10supporting
confidence: 59%
“…18 By contrast, functional disability is closely associated with the severity of motor symptoms, 16 and standardized rating scales are currently being used to measure disease progression in MSA experimental trials. 19 -21 Given the variability inherent in such clinical descriptors, alternative quantifiers of disease severity/progression may enhance the accuracy and speed of experimental trials of new MSA therapies.…”
Section: Discussionmentioning
confidence: 99%
“…31 Motor and autonomic features lead to major disability. Early autonomic failure; older age of onset; short interval from disease onset to frequent falling, cognitive disability, unintelligible speech, severe dysphagia, dependence on wheelchair for mobility, and urinary catheter use; and lack of admission to a nursing home facility independently predict short disease survival.…”
Section: Natural Historymentioning
confidence: 99%
“…The mean disease duration from onset to death is about 7 years. 31 Progressive supranuclear palsyparkinsonism. In contrast to patients with PSP-Richardson syndrome, PSPparkinsonism patients develop bradykinesia and limb rigidity at disease onset, which can be asymmetric and, in some cases, associated with a jerky action or rest tremor.…”
mentioning
confidence: 99%